Absolute beginners: Ukulele (the complete picture guide to playing the ukulele written by steven sproat) - Sproat, Steven (Wise London, 2007)
Features step by step pictures that take you from the first day exercises to playing along with a backing track. Designed to tell you what you need to know, this book uses pictures instead of long explanations. It also includes CD audio tracks to show you how things should sound, and full length accompaniment tracks to play along with.